Rice glycosyltransferase DUGT2 enhances drought and salt tolerances through glycosylating a broad-spectrum of flavonoids under bZIP16 regulation - Dong, Guangrui (Plant science : an international journal of experimental plant biology, 2025)
Copyright © 2025 Elsevier B.V. All rights reserved.